Formation of general professional competencies in bachelores of pedagogical education in the process of mastering additional educational programs - Gavrilova, Nellie Gennadievna (Razvitie obrazovaniâ (Online), 2023)
The emergence of new public policy priorities in the field of education changes the role of lifelong education in the system of socialization of the individual, as well as the nature of interaction between various subjects within the educational process and beyond. To increase competitiveness in the labor market, students of higher educational institutions need to be prepared to quickly master new knowledge and skills to meet the requirements of professional activity in the labor market. One of the forms of obtaining specific knowledge and skills for students in parallel with higher education is additional education. The purpose of the study is to analyze the pedagogical conditions for the formation of general professional competencies among bachelors of pedagogical education using additional education programs. Materials and methods of research. The research materials are the methodologically based on a scientific review of research approaches developed in domestic pedagogy in the field of improving the system of training generalist specialists in the development of additional education programs. The research methods are the study and analysis of scientific and methodological literary sources, as well as questioning of students. Research results. At the Chuvash State Pedagogical University named after I.Ya. Yakovlev Center for Continuing Education. To determine the possibility of additional professional education, a study was conducted among students of this university in order to identify their awareness of the possibilities of mastering additional education programs. The results of the survey, according to which many students plan to undergo additional education in standard programs, 20% plan to receive certificates or certificates in a whole range of programs. Conclusions. The system of additional education adapts future teachers to the specifics of modern socio-economic conditions, high demands from the labor market and, ultimately, forms a highly qualified specialist with a wide profile, capable of a continuous process of self-improvement in the process of professional activity.